Advanced volar locking plate fixation for intra and extra articular distal radius fractures: a retrospective study - Giuseppe Rovere; Francesco Bosco; Giulio Vigni; Ennio Sinno; Andrea Perna; Fortunato Giustra; Francesco Liuzza; Amarildo Smakaj; Fernando De Maio; Antonio Ziranu; Giuseppe Tulumello; Lawrence Camarda (Medicinski glasnik, 2026)
Background Distal radius fractures are among the most common orthopedic injuries, posing significant challenges due to their high prevalence and potential for long-term functional impairment. Volar locking plates have emerged as the gold standard for managing unstable and extra-articular fractures, offering superior outcomes compared to traditional methods. This study evaluates the clinical, radiographic, and functional outcomes of volar locking plate fixation in 34 patients with intra and extra-articular distal radius fractures. Methods: This retrospective study analyzed 34 patients treated for intra and extra-articular distal radius fractures with volar locking plates at a single orthopedic center. Patients were followed for a mean duration of 24 months (range: 12-36 months). Outcomes were assessed using the Disabilities of the Arm, Shoulder, and Hand (DASH) score, Visual Analog Scale (VAS) for pain, range of motion (ROM), and radiographic parameters. Complications, including hardware-related issues and soft tissue irritation, were recorded. Statistical analysis compared preoperative and postoperative outcomes, with significance set at p < 0.05. Results: The mean DASH score at the final follow-up was 4.2 ± 1.8, reflecting excellent functional recovery. Pain relief was complete, with all patients reporting a VAS score of 0. ROM restoration was highly satisfactory, achieving 93-98% of contralateral wrist motion. Radiographic evaluations confirmed 100% fracture consolidation with no cases of malunion or nonunion. Complications were minimal, with only two patients experiencing transient soft tissue discomfort, managed conservatively. No tendon irritation or hardware-related complications were observed. Conclusions: Volar locking plate fixation for intra and extra-articular distal radius fractures demonstrated excellent clinical, functional, and radiographic outcomes in this cohort of 34 patients. The low-profile design and anatomical contouring of modern plates minimized complications while promoting effective pain relief and rapid functional recovery.
Keywords: Distal radius fractures; Volar locking plates; Extra-articular fractures; Fracture fixation; Range of motion; DASH score